On the Origin of Jupiter’s Fuzzy Core: Constraints from N-body, Impact, and Evolution Simulations - Thomas Meier; Christian Reinhardt; Sho Shibata; Simon Müller; Joachim Stadel; Ravit Helled (The Astrophysical Journal)
It has been suggested that Jupiter’s fuzzy core could be a result of a giant impact. Here, we investigate the expected impact conditions from N -body simulations. We then use state-of-the-art smoothed particle hydrodynamics simulations to investigate the results of impacts with different conditions including various impactor masses and composition, different formation stages in Jupiter’s growth, and different resolutions. We next simulate the long-term thermal evolution of Jupiter postimpact. We find that 3D N -body simulations predict rather oblique impacts, and that head-on collisions are rare. Moreover, our results show that, even under a head-on collision, Jupiter’s fuzzy core cannot be formed. We next simulated Jupiter’s thermal evolution and showed that, unless postimpact temperatures are extremely low, a giant impact would not lead to an extended dilute core as inferred by interior models. We conclude that Jupiter’s fuzzy core is not caused by an impact and is likely to be an outcome of its formation process.